Kajian Penggunaan Media Visual Berbasis Education Game pada Pembelajaran Fisika Materi Jarak, Kecepatan dan Percepatan - Siti Khoirunnisa; Yulianah Yulianah; Agung Windrianto; Bunga Bunga; Rina Hidayati Pratiwi (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Generally, students stated that the concepts in physics, especially on the material of distance, speed, and acceleration, are difficult to understand. This causes low student motivation and learning outcomes. In order to increase student motivation, understanding of concepts, and learning outcomes, it is necessary to use visual media so that learning is active and enjoyable. The use of visual media, one of which is education game-based learning media, is very helpful for students in understanding physics concepts, especially on the material of distance, speed, and acceleration. The purpose of this study was to determine the study of the use of visual media based on education games that can improve students' understanding of the material of distance, speed, and acceleration. This research method uses the library research method. The form of research uses literature studies with qualitative data acquisition. To obtain data using two databases, namely Google Scholar and Sinta, with document analysis first carried out to identify relevant literature studies. Based on the results of the preliminary study conducted, it was obtained that the use of visual media based on education games is good and flexible. With the use of visual media based on education games, students find it easier to understand the material of distance, speed, and acceleration. In addition, it makes it easier for teachers to carry out learning activities. Learning is more interesting, students are more motivated so that students' understanding, abilities, and learning outcomes increase.